Two-fluid modeling of direct steam generation in the receiver of parabolic trough solar collector with non-uniform heat flux - Pal, Ram Kumar; K., Ravi Kumar (Energy (Oxford), 2021)
In this study, the thermo-hydrodynamics of direct steam generation in the receiver of parabolic trough solar collector have been investigated using a two-fluid modeling approach. The numerical models for solving the conservation equations, turbulence parameters, phase change, boiling heat transfer, and heat loss from the receiver have been discussed in detail. The three-dimensional governing equations are solved for 12 m length of the parabolic trough solar collector using ANSYS Fluent 2020R1. The receiver is modeled with and without considering the glass envelop. The thermal-hydraulics of the direct steam generation process is studied at solar noontime and 2 h before and after solar noon with direct normal irradiance (DNI) of 750 W/m2. Further, the effect of inlet mass flow rates and operating pressures have been investigated. The simulations are performed for mass flow rates 0.3 kg/s to 0.6 kg/s and operating pressure 30 bar–100 bar. The simulation results have shown that the vapor volume fraction at the absorber outlet varies in the range of 0.30–0.58 without considering the heat losses. The absorber’s outer surface temperature reached the maximum temperature of 526.5 K, 568.1 K, and 603.4 K, respectively for operating pressures 30 bar, 60 bar, and 100 bar at solar noon. The maximum circumferential temperature difference is observed 16 K during the solar noon. The increments in mixture velocity from inlet to outlet are observed as 0.76 m/s, 0.41 m/s, and 0.26 m/s, respectively for operating pressure 30, 60, and 90 bar at the solar noon. The relative velocity between the liquid and vapor phase have been predicted. The higher pressure drops are observed at the lower operating pressures. The average heat loss from the receiver is observed as 95 W/m2 for operating pressure 30 bar and MFRs 0.3 kg/s to 0.6 kg/s and the absorber surface temperature varies between 506 K and 525 K. Further the comparison of thermal-hydraulic parameters with and without considering the glass envelop is presented. The comparison of thermal-hydraulic parameters for solar heat flux corresponding to solar noon and 2 h before and after the solar noon are presented. •Two-fluid modeling is explored for direct steam generation in PTC.•Modeling of solar heat flux partition and mass transfer discussed.•Thermal behaviour of the absorber of the PTC is analyzed for various operating conditions.•The circumferential temperature distributions around the absorber surface are plotted.•Thermal-hydraulic behaviour of DSG at solar noon and 2 h before solar are compared.